Impact of virtual patient engagement on glycemic control in type 2 diabetes: a retrospective observational study from GluCare hybrid care model - Zakaria, Hala; Paul, Geethu; Debs, Joelle; Ali, Juman; Almarzooqi, Adam; Hashemi, Ali; Almarzooqi, Ihsan (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM), a chronic metabolic disorder requiring sustained glycemic control to prevent complications. Traditional in-clinic care often limits patient engagement to periodic visits, leaving gaps in continuous diabetes management. Digital health interventions, including virtual two way patient engagement between patients and the care team may enhance adherence and outcomes. However, the impact of different engagement modalities on glycemic control remains underexplored. This study evaluates the impact of virtual patient engagement within the GluCare hybrid care model on glycemic control in individuals with T2DM.MethodsThis retrospective observational study included T2DM patients(n=125) enrolled in GluCare’s hybrid care program. Participants were stratified into two groups based on glycemic control: controlled (HbA1c <7%) and poorly controlled (HbA1c ≥7%). Patient engagement was categorized into inbound (patient-initiated) and outbound (provider-initiated) interactions. Clinical and metabolic parameters, including HbA1c, blood pressure, lipid profile, inflammatory markers, renal function, and anthropometric measures, were assessed at baseline and 12 months.ResultsParticipants in the poorly controlled group exhibited a mean HbA1c reduction of −2.4% (p < 0.001), while controlled patients improved −0.3% (p < 0.001). This magnitude exceeds the −0.3% to −0.5% typically reported for digital-only interventions, indicating clinically meaningful improvement. The higher number of virtual interactions was associated with improved glycemic control (β = –0.007; 95% CI: –0.011 to –0.002; p = 0.003) and remained significant after adjusting for age, BMI, medication use, and glycemic control group (β = –0.006; 95% CI: –0.010 to –0.002; p = 0.001). Both controlled and poorly controlled groups achieved similar HbA1c levels at 12 months (p = 0.205). Engagement peaked at 3 months and declined thereafter, with outbound interactions consistently exceeding inbound ones However, Poorly controlled group more prescribed on GIP/GLP-1 receptor agonists (59.6%), insulin (75%) and statin therapy (56.8%) compared to the controlled group.ConclusionVirtual patient engagement, particularly provider-initiated interactions, plays a crucial role in optimizing glycemic control and improving metabolic outcomes in T2DM. Hybrid care models that integrate continuous remote monitoring with periodic in-clinic visits offer a viable approach to sustaining patient adherence.